J48 Tree Classification and Simple K-Means Clusterization on the Behavior of Academic Community in Accessing Internet for Bandwidth Management Plan - Imron Iswanto; Abdul Ghofir (President University, 2023)
Abstract The purpose of the research was to review theimprovements in internet usage behavior by the academiccommunity at a university which consisted of favorite websitevariables, the amount of internet bandwidth capacity used andthe time spent accessing the website. The research wasconducted in a population of 200 lecturers and 5267 students.Internet bandwidth mapping is carried out using two methods ofthe J48 tree classification algorithm and simple K-Meansclustering contained in the WEKA software. The results of thisstudy are for the purpose of mapping internet bandwidth,determining internet service provider load balancing,classification and clustering of favorite websites based on timeduration which can affect the use of existing internet bandwidthcapacity systems.